Spatial assessment of sugarcane (Saccharurn spp. L.) production to feed the Komenda Sugar Factory, Ghana. Issue 11 (November 2018) - Yawson, David O.; Adu, Michael O.; Osei, Kingsley N.
Abstract: Ghana imports about US 2 million worth of sugar annually. To address this huge import bill and to take advantage of a growing demand for sugar in the West African sub-region, the Government of Ghana initiated a Sugar Policy. The Government of Ghana, therefore, re-constructed and commissioned the Komenda Sugar Factory in 2016 at a reported cost of US 35 million. The Komenda Sugar Factory can process 1, 250 tons of sugarcane per day (or 225, 000 tons per annum), but was shut down soon after the test run and commissioning. This raised considerable public outcry. Among the numerous reasons that were given, it was widely believed that the factory faced feedstock deficits. This study therefore applied satellite remote sensing and Geographic Information Systems to quantify the potential feedstock supply from current production within the immediate catchment of the factory. Supervised classification was applied to Landsat 8 images, using QGIS, to quantify sugarcane production in the study area and at specified buffer distances from the factory. The results showed that the factory could mobilize only 7% of its feedstock requirement within the industrially recommended radius of 40 miles and 13% within the entire catchment area in the 2016/2017 season. Thus, under current scale of production and production conditions, the Komenda Sugar Factory faces large deficits in feedstock supply. National production data suggests that total national sugarcane production in 2016 would only meet 68% of the factory's requirement if it were operational. The results suggest an urgent need to establish a plantation for the factory and to commit out-growers to production to support and sustain the factory if it is to become operational soon. There is also a need for high-yielding, high-brix, and early maturing varieties, coupled with good agronomic practices, to bridge the quantity and (potentially) quality gaps.